Theoretical study of the dynamics of molecular lasers in hybrid plasmon cavities using the theory of functional density and the main quantum equations - Thajeel , Sadeq Khudhur (International Journal of Aquatic Research and Environmental Studies, 2026)
We research on the new alternative of how we can produce small sources of light with a blend of metal and molecule. Metal box is referred to as cavity traps light within small space. Molecule sits in this space. Light strikes on the molecule and they are combing to be a single thing. We call this hybrid state. Target is to have very small and fast laser. We use computer mathematics to see things move. We employ theory referred to as QED-DFT which counts electrons and pushes them by light. We also employ equations referred to as Maxwell-Bloch to time. It is found that laser is fast to turn on when there is a strong mixing. appear, and that light come out coherent. This we check by examining photon statistics. We also check whether laser functions under hot room conditions. Simulation establishes that device is stable. This work has been useful in developing future chips that will be light based rather than wire based.